Hybrid regulation for the enhanced mechanical properties of laser powder bed fused AlSi10Mg alloy: Remelting with laser shock-based SiC implantation - Jiantao Zhou; Xiao Yang; Wei Shen; Gai Wu; Fang Dong (Materials & Design)
Laser powder bed fusion (LPBF) has been one of the most widely used additive manufacturing (AM) technologies. However, the LPBF-built AlSi10Mg alloy is still restricted by the mechanical performance. In this work, a hybrid laser regulation method combining in-situ laser remelting (LSR) and ex-situ laser shock-based SiC implantation (LSI-SiC) was proposed. The experiments demonstrated that the compressive residual stress with the value of 72 MPa was obtained with weaken surface flatness after hybrid laser regulation. Nanoscale grains were presented with obvious dislocation tangle. The high tensile strength (492 MPa) was achieved while maintaining good ductility (4.5 %) attributed to various strengthening effects. The numerical results showed that the dislocation and atomic stress were more sensitive for the size and shape of nanoscale SiC. This work provides a novel guidance for simultaneously enhancing the strength and ductility of AlSi10Mg alloy via effectively combining in-situ and ex-situ laser regulation.